Analysis Factor Safety of Slopes With Sandy Loam Soil Types on Conditions Not Saturated, Saturated Conditions and Partially Saturated Conditions Using Computing Program - Saputra, Datra Peta; Afriani, Lusmeilia; Zakaria, Ahmad (Universitas Lampung, 2020)
Natural disasters often occur in hilly areas in Lampung Province, namely landslides. Landslides that occur due to increased pore water pressure. The 2012 GeoStudio SLOPE / W program can analyze slope stability that can be modeled according to the original conditions in the field and can know the value of the safe slope factor. In this study, there were three cross section slopes with three groundwater conditions, namely the condition of the groundwater level at the base of the slope, half the height of the slope and following the maximum height of the cross section of the slope. Land property data needed include : cohesion, shear angle in soil and weight of soil contents. Slope stability is achieved when the retention force is greater than the driving force. The results of the analysis of slope stability show that the condition of the groundwater is very influential on slope stability, can be seen from the results of GeoStudio SLOPE / W 2012 analysis in simulation 1 and simulation 2 safe factor values obtained >1.25 that is slopes are in safe status, while in simulation 3 the saturated condition has a safe factor <1,25 that is unsafe slopes or landslides, it is recommended to take care to prevent landslides. Key words : soil, slope stability, safety factor, geostudio slope/w 2012